Efficiency calculation by Monte Carlo simulation for the rapidly-deployable spectrometric air-sampling system (MARE). (15th September 2021) - Alegria, N.; Legarda, F.
Abstract: In order to get information about the concentration of gamma emitting radionuclides at ground level in case of a nuclear or radiological accident or incident, sampling devices have been designed in the framework of the European Metrology Programme for Innovation and Research (EMPIR) of the European Association of National Metrology Institutes (EURAMET) [1] financed Preparedness project. To fulfill its duty, the device must be properly calibrated in efficiency so as to relate spectra to activity concentration taking any modifying factor, such as coincidence summing correction, into account. Experimental approach to efficiency calibration is a prohibitively difficult task, so the Monte Carlo simulation method has been successfully adopted.